Paroxysmal Atrial Fibrillation Induced by Ice-Cold Water Ingestion in a Triathlete: A Case Report - Scarfò, Giorgia (Am J Case Rep, 2021)
Patient: Male, 35-year-old Final Diagnosis: Swallowing-induced atrial fibrillation Symptoms: Atrial fibrillation Medication: — Clinical Procedure: — Specialty: Cardiology • Sports Medicine OBJECTIVE: Unknown ethiology BACKGROUND: Swallowing-induced tachyarrhythmias are rare, and their possible mechanisms are still not completely elucidated. Even though a mechanical stimulation has been suggested, involvement of the autonomic nervous system has not been completely excluded. Moreover, tachyarrhythmias are not so frequent in athletes. CASE REPORT: We present a case of a 35-year-old male triathlete who reported palpitations after swallowing ice-cold water following physical activity. His physical examination and basal electrocardiogram were essentially normal. The 24-h Holter monitoring showed a sinus rhythm with sporadic isolated supraventricular ectopic beat and a 2-h run of atrial fibrillation (160–200 beats/min). This episode of paroxysmal atrial fibrillation was related to and occurred after the ingestion of ice-cold water following physical exercise. We were able to reproduce this event. Notably, the tachyarrhythmia was only triggered by swallowing ice-cold water; nothing happened with room-temperature water. No therapy was given to the triathlete to avoid influencing his physical performance in any way. CONCLUSIONS: This case suggests that both an esophageal mechanical stimulation and autonomic nervous system involvement were at the base of this tachyarrhythmia. The influence of water temperature on the esophageal thermoceptors has to be considered.